2019
DOI: 10.11591/edulearn.v13i3.9907
|View full text |Cite
|
Sign up to set email alerts
|

Development of Problem-based Blended Learning (PB2L) model to increase pre-service primary teacher’s creative thinking skill

Abstract: Problem-based learning is generally done with face-to-face interaction. This learning process, however, has not provided a lot of time for learners to find limitless and timeless information and learning resources. It still depends on the teacher as a source of information. Students are very dependent on the presence of lecturers during face-to-face interaction. This research aims to develop a Problem-based Blended Learning (PB2L) model to support student to improve their creative thinking skills. The method u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Furthermore, the study recently found that problem-based blended learning and learning outcomes had a significant impact on students' learning outcomes in accounting classes. It strengthened the previous study conducted by Waluya et al, (2019) revealing that problem-based blended learning improved students' creative thinking skills reflected on their learning achievement. A similar finding was also discovered in the study conducted by Ismail and Edi (2022) in which problem-based blended learning was perceived as an effective learning method for increasing students' reading skills obtained from their learning outcomes in reading class.…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, the study recently found that problem-based blended learning and learning outcomes had a significant impact on students' learning outcomes in accounting classes. It strengthened the previous study conducted by Waluya et al, (2019) revealing that problem-based blended learning improved students' creative thinking skills reflected on their learning achievement. A similar finding was also discovered in the study conducted by Ismail and Edi (2022) in which problem-based blended learning was perceived as an effective learning method for increasing students' reading skills obtained from their learning outcomes in reading class.…”
Section: Discussionsupporting
confidence: 78%
“…Learners' creativity in contextual teaching and learning is observed in several stages of learning aspects of creativity that can be seen, including curiosity. Improving the science process skills of innovative learners from teachers becomes a top priority [35], [36]. Applying contextual teaching and learning methods makes positive changes in learners [37].…”
Section: Resultsmentioning
confidence: 99%